Evidences for endophytes parasiting traditional clones of cassava (Manihot esculenta Crantz) - Rivera, M.F.; Laberry Saavedra, Rafael Alberto; Lozano, J.C. (International Center for Tropical Agriculture, 1993)
The existence of endophytes in cassava was suspected for the following reasons: (a) A wide range variation of root yield is frequent among disease-symptomless plants growing on the same plot; (b) root yield of low-yielding, virus-free plants of traditional clones can be increased by meristem culture; (c) the performance (i.e. root yield) of meristem-culture derived plants decreases sharply and uniformly under field conditions; and (d) the long growing cycle of cassava and its vegetative propagation allow infection and dissemination of these parasites. The existence of endophytes affecting cassava was demonstrated by the following: (a) Several fungal species were isolated from internal tissues of the epidermis, colenchyma and parenchyma of stems of symptomless low-yielding plants of various clones. Most of these species have been reported as endophytes in the literature; (b) inoculation on plantlets and callus tissues did not induce visible symptoms, but inoculated fungal species were reisolated from internal tissues near the inoculated points 30 days afterwards; (c) total root dry weights (Vha) of plots planted with stakes taken from commercial fields and treated with a systemic fungicide were higher than for similar plots treated with a protectant fungicide or untreated controls; and (d) histological studies observing fungal invasion into the host tissues have shown hyphal growth in colenchyma and parenchyma tissues of affected stems. Additionally, the existence of beneficial endophytes is suspected; this could be of importance to increase biomass production or induce plant protection against detrimental parasites.